Determinants of Subjective Well-Being among the Elderly Population: A Cross-Sectional Study in Thai Communities - Huaisai, Wuttichan; Songsin, Niwat; Chusuton, Sarayut; Somporn, Kanokporn; Chamnankit, Tossapon (National Journal of Community Medicine, 2025)
Introduction: Happiness is a crucial quality-of-life indicator for the elderly, aligning with Thailand's core national development goal of well-being. Methods: This cross-sectional study assessed the happiness levels and associated determinants among 313 elderly individuals in Samut Songkhram Province, Thailand. Data were collected via questionnaires using stratified random sampling and analyzed using descriptive statistics and stepwise multiple linear regression. Results: The study involved 313 elderly participants (mean age: 72.09 ± 8.14 years). The majority were male (56.87%), married (57.19%), and had attained primary education (56.23%). The median monthly income and expenditure were 5,000 Baht (IQR = 6,000) and 4,000 Baht (IQR = 4,500), respectively. A significant proportion (71.88%) did not have chronic diseases. The mean ADL score was 17.98 ± 2.70, and the mean self-efficacy score was 27.17 ± 6.31. Most participants reported moderate levels of enabling factors (51.44%) and reinforcing factors (49.20%). Happiness levels were comparable to the general population (43.45%). Income, ADL score, reinforcing factors, and self-efficacy were identified as significant predictors of happiness (p < 0.05), collectively explaining 15.46% of the variance in happiness. Conclusion: Optimal elderly happiness requires an integrated approach addressing key determinants including income, health, and multi-level social support (family, community, and society).